2021
DOI: 10.1161/jaha.120.020734
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Glucagon‐Like Peptide‐1 Receptor Ameliorates Cognitive Decline in Type 2 Diabetes Mellitus Through a Metabolism‐Independent Pathway

Abstract: Background Patients with hypertension and diabetes mellitus are susceptible to dementia, but regular therapy fails to reduce the risk of dementia. Glucagon‐like peptide‐1 receptor agonists have neuroprotective effects in experimental studies. We aimed to assess the effect of liraglutide, a glucagon‐like peptide‐1 receptor agonist, on cognitive function and whether its effect was associated with metabolic changes in patients with type 2 diabetes mellitus. Methods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Ten studies that did not meet the inclusion criteria, three studies with incomplete data, and seven studies that did not meet the outcome criteria were excluded. Finally, 13 relevant studies were included ( Hanyu et al, 2009 ; Plastino et al, 2010 ; Sato et al, 2011 ; Cukierman-Yaffe et al, 2014 , 2020 ; Guo et al, 2014 ; Isik et al, 2017 ; Köbe et al, 2017 ; Furie et al, 2018 ; Lin et al, 2018 ; Biessels et al, 2021 ; Cummings et al, 2021 ; Li et al, 2021 ). The specific literature screening process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies that did not meet the inclusion criteria, three studies with incomplete data, and seven studies that did not meet the outcome criteria were excluded. Finally, 13 relevant studies were included ( Hanyu et al, 2009 ; Plastino et al, 2010 ; Sato et al, 2011 ; Cukierman-Yaffe et al, 2014 , 2020 ; Guo et al, 2014 ; Isik et al, 2017 ; Köbe et al, 2017 ; Furie et al, 2018 ; Lin et al, 2018 ; Biessels et al, 2021 ; Cummings et al, 2021 ; Li et al, 2021 ). The specific literature screening process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 34 articles were eligible for full-text review and data assessment. A total of 5 studies comprising three randomized controlled trials ( 18 – 20 ) and two prospective cohort studies ( 21 , 22 ) that met the inclusion criteria were analyzed ( Figure 1 ). Consequently, a “snowball search” was performed based on the citation lists of all the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were seen with PC12 cells, as GLUT3 expression was significantly inhibited by BAPT-AM and Compound C but increased upon AMPK activation by AICAR. We recently showed that the GLP-1 receptor agonist, liraglutide, can improve the cognitive function of patients with type 2 diabetes mellitus ( 49 ). Thus, the protective effects of hyperforin on cognitive function should be further tested in patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%